ChemInform Abstract: Construction of Multisubstituted Tetrahydropyrans by a Domino Oxa‐Michael/Tsuji—Trost Reaction. Issue 23 (16th May 2013) - Wang, Liang; Menche, Dirk
Abstract Pd‐catalyzed treatment of unsaturated alcohols of type (I) with nitro olefins provides a new and efficient approach to multisubstituted tetrahydropyrans, which are of synthetic and biological interest.